The Benefits of Plant-Based Diets in Lowering Cholesterol Levels and Promoting Heart Health - Icha Elyanida (Mandalika Journal of Medical and Health Studies, 2025)
This article examines the benefits of plant-based diets in lowering cholesterol levels and promoting heart health. A growing body of evidence suggests that diets rich in fruits, vegetables, whole grains, legumes, nuts, and seeds can significantly improve lipid profiles and reduce the risk of cardiovascular diseases. The mechanisms through which plant-based diets exert their effects include the high content of dietary fiber, antioxidants, and healthy fats, which collectively contribute to the reduction of low-density lipoprotein (LDL) cholesterol and inflammation. Furthermore, the article discusses the role of specific plant-based foods, such as oats, beans, and avocados, in heart health, highlighting their ability to enhance endothelial function and improve overall cardiovascular outcomes. By adopting a plant-based dietary pattern, individuals can not only lower their cholesterol levels but also embrace a lifestyle that supports long-term heart health.